(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Refugees and asylum seekers are susceptible to developing common mental disorders due to their exposure to stressful experiences before, during and after their flight. The Syrian Civil War, which started in 2011, has led to a massive number of Syrians seeking refuge and asylum in European countries, including Switzerland. Currently, Syrians are the second-largest refugee and asylum-seeking population in Switzerland. However, very little is known about the problems faced by this new population in Switzerland and their needs relating to mental health services. Identifying the problems faced by this community is crucial to providing adapted and tailored mental health services to Syrian refugees in Switzerland. AIM OF THE STUDY The current study aimed to identify problems that Syrian refugees and asylum seekers face daily while living in Switzerland in order to inform the adaptation of a brief psychological intervention. METHODS We used a cross-sectional, qualitative design and collected data according to The Manual for Design, Implementation, Monitoring and Evaluation of Mental Health and Psychosocial Assistance Programs for Trauma Survivors in order to identify problems perceived by the target population. Free-listing, open-ended interviews were conducted with 30 adult Syrian refugees and asylum seekers and analyzed using thematic analysis. RESULTS The results show that besides physical health problems, Syrians experience primarily two types of problems: practical and psychological (emotional) problems. These two types of problems are closely interrelated. The most common practical problems (problems with government and authorities, problems related to residence permits, problems with integration, cultural differences, language problems, problems related to education, problems related to employment, and problems with housing) were reported by almost half of all participants. Symptoms of mental disorders and feelings of uncertainty, frustration and injustice were the most common psychological problems and were mentioned by more than one third of the participants. The finding that almost half of the participants reported typical symptoms of mental health disorders suggests that a considerable number of Syrian refugees and asylum seekers might need mental healthcare. CONCLUSIONS Authorities, practitioners and researchers should recognize that Syrian refugees and asylum seekers are strongly affected by a broad range of problems. Besides practical problems, they suffer a multitude of psychological problems, and a significant number of them report, among other issues, symptoms of mental health disorders. Officials working with this population should be aware of this vulnerability and be prepared to refer clients in need of mental healthcare to mental healthcare providers. Moreover, the significant variety and number of problems experienced by this population should be taken into consideration when developing solutions tailored to their needs.